BACTERIAL PROFILE AND ANTIBIOGRAM PATTERN OF UTI IN PREGNANT WOMEN AT TERTIARY CARE TEACHING HOSPITAL - NITHYALAKSHMI J.; VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2014)
Urinary Tract Infection is a common medical complication of pregnancy. UTI is of great clinical concern in this group, as it has adverse maternal and obstetric outcomes. The changing pattern of antimicrobial resistance of uropathogens is a growing problem. Knowledge about the current trends of bacterial profile and their antibiogram pattern in pregnant women may help the clinician to choose the appropriate regime.The aims of this study were to assess bacterial profile that causes UTI among pregnant women and to determine the resistance patterns of urinary isolates in our region.Three hundred and three pregnant women with asymptomatic and symptomatic UTI were included in this study from March 2012 to march 2013. Samples were processed and isolates were identified as per the CLSI guidelines. Antibiotic susceptibility was done by kirby bauer disk diffusion method.The overall prevalence of UTI in pregnant women was 14.19%. The age range of the study group was 20 to 42 years. Screening for uropathogens by the gold standard culture technique revealed that 14.77% and 10.25% of the total midstream urine samples had significant bacteriuria in asymptomatic and symptomatic group. The predominant bacterial pathogens were E. coli (65.11%) followed by Klebsiella pneumonia (11.62%), Staphylococcus aureus (11.62%) and Proteus mirabilis (4.65%). The gram positive and gram-negative bacteria accounted for 18.6% and 81.39% respectively. The susceptibility pattern of gram negative bacteria showed that most of the isolates (>70% of the isolates) were sensitive to Norfloxacin, Ceftriaxone and Augmentin. Resistance to amoxicillin and cotrimoxazole was significant in all isolates. In this study the gram negative isolates showed a low degree of susceptibility to Gentamicin (22.85%) and Amikacin (25.71%). Among the gram positives, more than 75% of the isolates were sensitive to Ampicillin, Ciprofloxacin, Norfloxacin, Gentamicin, Amikacin , Ceftriaxone and Augmentin.Significant bacteriuria was observed both in symptomatic and asymptomatic pregnant women. Antimicrobial sensitivity pattern of isolated uropathogens showed a changing pattern,so we recommend periodic monitoring of resistance pattern and development of specific guidelines based on local susceptibility patterns, as this would prevent the spread and further development of resistant strains eventually.